2017
DOI: 10.1001/jamaoto.2016.3353
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adjuvant Chemotherapy in Surgically Managed, p16-Positive Oropharyngeal Squamous Cell Carcinoma

Abstract: IMPORTANCE Human papillomavirus (HPV)-related oropharyngeal squamous cell carcinoma (OPSCC) has a favorable prognosis, and p16 immunohistochemistry is a surrogate marker of high-risk HPV infection and strong prognosticator. Given this favorable prognosis, treatment de-escalation for p16-positive OPSCC is now being considered with the goal of decreasing treatment-associated morbidity without compromising tumor control. The role of adjuvant chemotherapy in this setting is becoming increasingly unclear. OBJECTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…The extent of ECS was not graded for this study; however, in a previous publication that included nearly all patients from the current study cohort, application of ECS grading showed the highest grade of ECS (graded STM) to associate with reduced DFS. Administration of adjuvant therapy associated with improved DFS, and reduced number of recurrences correlative with our recently published matched study by Jackson et al However, addition of chemotherapy to postoperative radiation did not associate with additional benefit corroborating findings from the thesis and other reports on HPV‐related OPSCC, some of which include national cancer database analyses . The median (range) adjuvant radiation dose at the primary, ipsilateral, and contralateral neck in our study cohort was 66 (48–70), 66 (36–70), and 56 (45–66) grays (Gy).…”
Section: Discussionsupporting
confidence: 90%
“…The extent of ECS was not graded for this study; however, in a previous publication that included nearly all patients from the current study cohort, application of ECS grading showed the highest grade of ECS (graded STM) to associate with reduced DFS. Administration of adjuvant therapy associated with improved DFS, and reduced number of recurrences correlative with our recently published matched study by Jackson et al However, addition of chemotherapy to postoperative radiation did not associate with additional benefit corroborating findings from the thesis and other reports on HPV‐related OPSCC, some of which include national cancer database analyses . The median (range) adjuvant radiation dose at the primary, ipsilateral, and contralateral neck in our study cohort was 66 (48–70), 66 (36–70), and 56 (45–66) grays (Gy).…”
Section: Discussionsupporting
confidence: 90%
“…Among patients receiving adjuvant chemotherapy, smoking reduced progression-free survival and overall survival in ovarian cancer [52]. The similar poor prognosis has also been confirmed in HNSCC [53]. Mechanically, Ye et al [54] recently found that smoking increased the expression of the TM4SF1 gene, which promotes NSCLC proliferation, invasion, and chemo-resistance through regulation of the DDR1/Akt/ERK-mTOR axis.…”
Section: Discussionmentioning
confidence: 82%
“…12 Sinha and Skillington both found that smoking negatively affected DFS in ever versus never smokers (HR, 2.3; 95% CI, 1.12-4.76; P = .023; HR, 3.42; 95% CI, 1.61-7.26; P \ .05). 9,12 Haughey also reported that current versus never smoking negatively affected DFS (HR, 5.25; 95% CI, 1.39-19.85; P = .014) but did not find a significantly increased risk for DSS. 13 Kaczmar et al did not find a significantly increased risk of disease recurrence using the 10-pack year smoking threshold.…”
Section: Surgical Management and Smokingmentioning
confidence: 98%